Remembering Prof Sayed Sikandar Shah Haneef - Abdul Razak, Mohd Abbas (Mission Soft Foundation, 2023)
Though many people come and go in our lives, only a few occupy a special place in our hearts. There can be a thousand and one reasons why an individual is remembered even after they are gone from this world. There is an ancient word of wisdom that says, ‘when great personalities leave this world, they only vanish physically from our sight while leaving something precious in the minds and hearts of people’. Analogically explained, any such great and impactful person is like a precious stone that breaks into thousands of pieces, and every tiny piece of his/her goodness stays in the hearts of people who love him/her. Such a great personality lives beyond death in the hearts of the people. At the International Islamic University Malaysia, where I teach, one is bound to come across great men of knowledge, wisdom, philosophy and personality. As a reputed learning institution, this university acts as a platform for the meeting of the great minds of the Muslim world. As a garden of knowledge and virtue, IIUM is quite successful in producing many remarkable young scholars, leaders and professionals who are now positioned in many parts of the world. As a student and now as a teaching staff of IIUM, I truly believe that this university which is the pride of the Ummah is one of the best learning institutions available in the Muslim world.